A study on maritime jurisdiction between Malaysia and Singapore: Pedra Branca Island / Auzan Syaidi Abdul Lateh ...[et al.] - Abdul Lateh, Auzan Syaidi; Abdul Rasid, Amirul Asyraf; Hashim, Noor Haeme; Kassim, Yasmin (2011)
This project paper discusses the delimitation of territorial waters between Malaysia and Singapore specifically based on the case of Pedra Branca as well as the maritime jurisdiction surrounding it. The project paper outlines our research proposal which consists of basic layouts in conducting our research. It also comprises of the background of maritime jurisdiction before and after the introduction of United Nations Convention on The Law of the Sea (UNCLOS). Furthermore, this project paper explains present situation regarding territorial waters in Malaysia and Singapore which includes the applied laws and references by both nations and their dealing ^with an overlapping jurisdiction. It nevertheless also highlights the dispute on delimitation of territorial waters between Malaysia and Singapore specifically on the case of Pedra Branca. In addition, this project paper discusses the decision of the International Court of Justice (ICJ) which also comprises of dissenting judgments and separate opinions. Besides, it also emphasizes comments generated by legal publicists. Last but not least, the project paper focuses on the issue of maritime security and how Pedra Branca has an effect to it as well as methods to prevent future losses of maritime jurisdiction.